Case Report : Expanded-Spectrum Beta Lactamase-Producing Klebsiella pneumoniae in Burn Injury With Hospital Acquired Pneumonia - Putra, Oki Nugraha (Pharmaceutical Journal of Indonesia, 2020)
Significantly higher mortality has been demonstrated in patients with severe burn, complicated by Klebsiella pneumonia infection. This case report assesses the efficacy combination of meropenem and levofloxacin to treat Klebsiella pneumonia ESBL on the scald-burn injury with hospital-acquired pneumonia. A 52-year-old male had scald burn on August, 2016 with late onset of Hospital Acquired Pneumonia (HAP). Klebsiella pneumonia ESBL was isolated from tissue burned culture. Initially, the patient was treated with meropenem and levofloxacin injection for a week. Then, Acinetobacter baumanii was isolated from tissue burned infection and ampicilin-sulbactam was the only one antibiotic which still susceptible to this pathogen. But with the clinical judgment, the combination of these antibiotics was still continued. After administration of these antibotics, rapid clinical improvement with signs short of breath, fever, cough was not observed and also the lung infiltrate was improved. The combination of meropenem and levofloxacin, may be a useful treatment option for hospital-acquired pneumonia related to Klebsiella pneumonia ESBL and also Acinetobacter baumanii, even these combination were resistance to Acinetobacter baumanii. Further research is also needed to clarify the effectiveness of meropenem and levofloxacin to treat Klebsiella pneumonia ESBL infection in the burn patient.